A theoretical investigation of S-Numerical Range with the respect to a family of projections - Hamad, Wlat; Botin Ibrahim (Zanco Journal of Pure and Applied Sciences, 2022)
The idea of the -numerical range of a bounded linear operator on a complex Hilbert space with respect to a family of projections is introduced in this study. We provide a detailed description and discuss its relationship to the -numerical range and generalizations such as product S-numerical range. The significance of this new concept comes from its unifying character.